Climate Change Indicators in the Al-Jufra Region: Analysis of Temperature Trends (2010–2024) - Dr. Mahmoud Mohamed Abdlmoula (Journal of Scientific and Human Dimensions, 2025)
Background and Aims: Desert regions like Al-Jufra in Libya are climate change hotspots due to their harsh climatic nature and sensitivity to thermal fluctuations. This study aimed to analyze climate change indicators in the Al-Jufra region by tracking monthly, annual, and seasonal temperature trends for the period 2010-2024, and assessing extreme temperature indices and their potential impacts. Methodology: The study relied on monthly maximum and minimum temperature data from the Hun meteorological station and NASA GISTEMP data. Descriptive, analytical, and statistical methods were employed, including the Mann-Kendall trend test, linear regression analysis, and calculation of seasonal indices and extreme temperature indicators (number of hot days, heatwave length). Results: The results showed a clear and steady upward trend in temperatures. The annual average maximum temperature increased from 32.1°C in 2010 to 41.9°C in 2024 (increase rate of 0.66°C/year), while the annual average minimum temperature increased from 12.4°C to 22.2°C (similar rate). The highest maximum temperature was recorded in July 2023 (46.61°C). An extension of the summer season to include April and October was observed, along with a noticeable increase in daily temperature variation and the number of very hot days (>40°C). Conclusions: The study confirms that the Al-Jufra region is experiencing rapid and tangible climate change, with a shift in seasonal patterns and an increased frequency of extreme events. These changes herald negative impacts on water resources, agriculture, the environment, and public health, necessitating urgent adaptation and mitigation measures.